Dampak Ekonomi Pengembangan Kawasan Wisata di Kabupaten Manokwari (Studi Kasus pada Kawasan Wisata Tanjung Papaya - Amban Pantai) - Alvany T Wanma; Rosmina Sasarari; Yomima D. Salamuk (Lensa Ekonomi, 2022)
The research was conducted in the tourist area of ​​Tanjung Papaya-Amban Pantai, Manokwari Regency. The tourism area began to develop rapidly since 2018 until now. In its development, several new businesses emerged such as homestays and cafes. The progress of the area certainly affects the lives of local people therefore this research was conducted to find out what kind of economic impact is felt by local residents from the use of this tourism area. The research was conducted using a qualitative (descriptive) method with the type of data collection through interviews with residents, residents are divided into two categories, they are entrepreneur and non-entrepreneur categories. The result of the research is the development of the tourism area has a positive economic impact on all residents. It showed by the increase of income for all resident of ​​Tanjung Papaya - Amban Pantai.